Modelling fuzzy multi-criteria decision-making method to locate industrial estates based on geographic information system - Mohammad Reza Jangjoo (Anthropogenic Pollution)
Existing conditions for locating urban equipment and facilities require a set of limiting and reinforcing factors. Interaction of environmental, industrial, social and political changes in our rapid growth adds to the complexity of regional systems. Locating takes place by various methods, in which the priority is the application of modern methods leading to reduced uncertainty. The present study aimed to select the best location using nine criteria (slope, distance from fault, distance from river, distance from road, and distance from villages, soil type, land use, average temperature, and average rainfall) in GIS software for mapping. Fuzzy logic and fuzzy-analytical hierarchy process (FAHP) model were applied to reduce location uncertainty. The accuracy of the results was checked using field data, in which six stations designated for the establishment of industrial estates in the study area were compared with the results of the FAHP model. The results of FAHP model in GIS software and their validation showed that the proposed model has excellent capabilities in locating industrial estates.